An empirical study of continuous participation intention in Chinese CrossFit participants: mediating roles of community belonging and sport commitment - Ji, Xuan; Wu, Qianjin (Frontiers in Psychology, 2025)
BackgroundMost existing CrossFit®-related studies focus on populations in Europe and North America, with limited attention to Chinese participants. In China, the sport’s promotion faces barriers such as high intensity and cost, highlighting the need to identify key factors influencing sustained participation.PurposeThis study investigates the influence of intrinsic exercise motivation on the intention for continuous participation among Chinese CrossFit participants. Specifically, it examines the mediating roles of sense of community belonging and sport commitment. Additionally, the study contributes Chinese samples to CrossFit research and provides theoretical and practical insights to help CrossFit facilities in China enhance operations and improve member retention.MethodsA total of 568 Chinese CrossFit participants were recruited through online CrossFit communities using a random sampling approach. A validated and reliable questionnaire was developed to assess exercise motivation, sense of community belonging, sport commitment, and continuous participation intention. Data analysis was conducted using SPSS and AMOS.Results and conclusionsIntrinsic exercise motivation positively influenced continuous participation intention (p < 0.001), sense of community belonging (p < 0.001), and sport commitment (p < 0.001). Sport commitment also positively affected continuous participation intention (p < 0.001) and mediated the relationship between motivation and participation. However, the sense of community belonging (p = 0.156) neither significantly influenced participation intention nor mediated the relationship between the two variables. These findings highlight the critical role of sport commitment while suggesting limited mediating effects of community belonging among Chinese CrossFit participants. Theoretically, this study develops an integrated model linking intrinsic motivation, mediating mechanisms (community belonging and sport commitment), and continuous participation intention. By incorporating belongingness theory and sport commitment theory into the CrossFit context, it extends existing motivational frameworks to a non-Western population and enriches cross-cultural perspectives on exercise adherence.